Upaya Peningkatan Pengetahuan Masyarakat Mengenai Perbedaan TBC dengan Covid-19 Melalui Program “Peduli TB Kenali Covid-19” di Nagari Jawi-Jawi Wilayah Kerja Puskesmas Talang - Sri Siswati; Mutia Mutia; Nindi Clorita M; Silvia Wulandari; Imelda Aliska; Mutiara Indah Pertiwi; Yuni Izmi Kurnia; Suci Pratiwi Maritim (Warta Pengabdian Andalas, 2021)
The current pandemic of Covid-19 causes many people to be afraid to go to the Public Health Centre because of requiring antigen/swab tests. Health Service Coverage data according to Minimum Service Standards (SPM) data at the health centre of Talang, people suspected of TB was still low, with a target of 386 cases in 2020. Based on the latest data in September 2021, it was found that the low coverage of pulmonary TB patients receiving treatment according to standards in Gunung Talang District was 19.83%. According to SPM (Minimum Service Standards), data on the coverage of suspected TB people at the Talang Health Center from January to September 2021 found 155 cases (40.15%), the lowest coverage in Nagari Jawi-Jawi was 17.72%. The cause of this data on the pulmonary TB problem is that several people hold too many programs, so the program is not monitored, and program holders do not focus on this problem. Meanwhile, when viewed from the perspective of society, many people do not understand the difference between pulmonary TB and Covid-19 infected—tuberculosis and Covid-19 attack the human respiratory tract both. Importance understanding the public about the differences between pulmonary TB and Covid-19 was needed.